2019
DOI: 10.1029/2019jd030833
|View full text |Cite
|
Sign up to set email alerts
|

An Ozone “Pool” in South China: Investigations on Atmospheric Dynamics and Photochemical Processes Over the Pearl River Estuary

Abstract: Pearl River Estuary (PRE) has been recognized as one of the key areas in South China experiencing severe air pollution. To understand the photochemical pollution over PRE, intensive measurements of O 3 and its precursors were simultaneously conducted at a suburban site on the east bank of PRE (Tung Chung, TC) in Hong Kong and a rural site on the west bank (Qi'ao Island, QAI) in Zhuhai from 25 September to 29 November 2016. Three and sixteen O 3 episode days (days with the maximum hourly O 3 higher than 100 ppb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 102 publications
2
20
0
Order By: Relevance
“…Although all sites showed good agreement with the observations, the peak values of O 3 concentration in GZ, ZQ, and DG during the O 3 episode were slightly underestimated. In the case of NO 2 , despite large bias existed in the WCR, the variations of NO 2 in most sites are well captured by the CMAQ simulation with IOA ranging from 0.52 to 0.71 and NMB values between 0.30 and 0.47, which were within the range (0.40–0.70) of acceptable model performance in literature (Wang et al., 2015; Zeren et al., 2019). These biases for O 3 and NO 2 are comparable with other modeling studies in PRD that have identified the uncertainty in emission inventory and bias in meteorological fields as primary causes (Hu et al., 2016; Ou et al., 2016; Wang et al., 2010).…”
Section: Resultssupporting
confidence: 54%
“…Although all sites showed good agreement with the observations, the peak values of O 3 concentration in GZ, ZQ, and DG during the O 3 episode were slightly underestimated. In the case of NO 2 , despite large bias existed in the WCR, the variations of NO 2 in most sites are well captured by the CMAQ simulation with IOA ranging from 0.52 to 0.71 and NMB values between 0.30 and 0.47, which were within the range (0.40–0.70) of acceptable model performance in literature (Wang et al., 2015; Zeren et al., 2019). These biases for O 3 and NO 2 are comparable with other modeling studies in PRD that have identified the uncertainty in emission inventory and bias in meteorological fields as primary causes (Hu et al., 2016; Ou et al., 2016; Wang et al., 2010).…”
Section: Resultssupporting
confidence: 54%
“…The reduction of observed O 3 ( O 3 ) in the early morning rush hour caused by NO titration did not appear, verifying the impacts of regional transport (X. Zeren et al, 2019;Chen et al, 2020). Due to the photochemical reactions, the precursors of CO, NO x , and VOCs were consumed during the daytime and were accumulated during the nighttime with weak solar radiation.…”
Section: Overview Of Observationsmentioning
confidence: 84%
“…Batchvarova et al [ 47 ] measured aerosol concentration at Ahtopol (Bulgaria) and found a lower number of coarse particles for marine air masses. Another example is the Pearl River Delta, where interactions of synoptic winds and mesoscale breezes determined weak winds and air pollution accumulation, favouring intense photochemical reactions and the formation of an ozone “pool” [ 48 ]. Similarly, in Manila, Philippines, strong sea breezes disperse fine particulate matter inland during the day in spring, although breezes are the outflow path of these aerosols during the night.…”
Section: Mesoscalementioning
confidence: 99%